Networks: From Biology to Theory - Feng, Jianfeng; Jost, Jürgen; Qian, Minping (Springer London : Imprint: Springer, 2007)
During the past decades, we have witnessed the thriving development of new mathematical, computational and theoretical approaches such as bioinformatics and neuroinformatics to tackle some fundamental issues in biology. These scientific approaches focus no longer on individual units, such as nerve cells or genes, but rather on the emerging dynamic patterns of interactions between them. These concentrate on the interplay between the local dynamics and activity transmissions on one side and the global structure of the underlying connection scheme on the other hand. In this light, the concept of a network emerges as a powerful and stimulating research paradigm in mathematics, physics and computer science, and demonstrates a very lively interaction between experimental findings, simulation studies, and theoretical investigations that then in turn lead to new experimental questions. This volume explores this concept in full and features contributions from a truly global set of contributors, many of whom are pre-eminent in their respective fields.